The influence of obedience pressure, independence, task complexity, and auditor experience on auditor judgment with auditee credibility as a moderating variable (Study at a public accounting firm in Medan, Indonesia) - M. Hadi Satrya Siregar (Indonesia Accounting Research Journal, 2023)
This research aims to analyze the influence of Pressure of Obedience, Auditor Independence, Task Complexity, and Auditor Experience on auditor's judgment with Auditee Credibility as a moderating variable in Public Accounting Firm in Medan. The population of this research is 12 Public Accounting Firm. This research is associative and data collection method is questionnaire method. Data analyze method in this research uses multiple linear regression method and residual test. The results showed that simultaneously Pressure of Obedience, Independence, Task Complexity, Experience Auditor significant effect on auditor’s judgment. Partial test shows that the Pressure of Obedience has a significant effect on auditor's judgment, Independence has no significant effect on auditor's judgment, Task Complexity has a significant effect on auditor's judgment and Auditor Experience has a significant effect on auditor's judgment. Testing of moderating variables with residual tests showed that Auditee credibility is not proven as a moderating variable that can moderate the Pressure of Obedience, Independence, Task Complexity, and Auditor Experience on auditor’s Judgment.